Indicators of Esophageal pH-Impedance Monitoring and High-Resolution Manometry in Patients with Various Forms of Gastroesophageal Reflux Disease - I. V. Maev; E. V. Barkalova; M. A. Ovsepyan; D. N. Andreev; Yu. A. Kucheryavyi (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim.  The aim of the study is to analyze the regularities of changes in the basic indicators of esophageal pH-impedance monitoring and high-resolution manometry in patients with non-erosive reflux disease (NERD), erosive reflux disease (ERD) and Barrett’s esophagus (BE) in comparison with healthy individuals.Materials and methods.  69 patients were examined, including 19 patients with NERD, 16 patients with ERD, 14 patients with BE and 20 individuals comprising the control group (CG). The gender structure was as follows: 44 male and 25 female patients. The average age of the examined patients was 46 years. All patients underwent 24-hour esophageal pH-impedance monitoring and high resolution manometry.Results.  According to the data of 24-hour pH-impedance monitoring, the total time in the esophagus with pH < 4 was 2.4 % in the control group, 9 % in the NERD group, 20.25 % in the ERD group and 23.5 % in the patients with BE (p < 0.05). The average number of acid refluxes was 22.5 in CG, 61 in the NERD group, 77 in the ERD group and 86 in patients with BE (p < 0.05). The time of chemical clearance was 1.7 minutes in CG, 2.2 minutes in the group of patients with NERD, 2.9 minutes in the ERD group and 3 minutes in the BE group (p < 0.05). The mean nocturnal baseline impedance was 2483.5 Ohm in CG, 1775.0 Ohm in the NERD group, 771.0 Ohm in the ERD group and 911.0 Ohm in the BE group (p < 0.05). The normal parameters of the esophagogastric junction (EGJ) structure and function according to the data of highresolution manometry were observed among 85 % of the control group, 63 % of patients with NERD, 25 % of patients with ERD and 36 % of BE group. The presence of hiatal hernia (HH) and/or hypotension of lower esophageal sphincter (LES) was observed in 15 % of patients from the CG, in 37 % of patients with NERD, in 75 % of patients with ERD and in 64 % of patients with BE. The normal parameters of the motor function of the esophagus were observed in CG (85 %), as well as in patients with NERD (79 %). In patients with ERB and BE, normal motor activity was noted in 25 % and 29 % of the cases, respectively. Disturbances of the motor function of the thoracic esophagus in CG were represented in 10 % of the cases by ineffective peristalsis and hypercontractility in the form of distal esophagospasm in 5 % of the cases. In the NERD group, 16 % of patients had ineffective peristalsis and 5 % of patients had hypercontractility in the form of a hypercontractile esophagus. In patients of ERD and BE groups, the disorders of the motor function of the thoracic esophagus were predominantly represented by ineffective peristalsis, in 75 % and 50 % of the patients, respectively. In addition, in the group of patients with BE, in 21 % of the cases, motor function disorders were observed in the form of absence of thoracic esophagus contractions.Conclusion.  It is shown that such indicators as increased level of acid exposure, increased amount of acid reflux, slowed chemical clearance, lowered mean nocturnal baseline impedance, as well as disorders in the structure and function of the esophageal-gastric junction and motility of the thoracic esophagus are associated with the severity of GERD.